2016
DOI: 10.1002/jor.23406
|View full text |Cite
|
Sign up to set email alerts
|

Sonication culture improves microbiological diagnosis of modular megaprostheses

Abstract: Modular megaprostheses are known for high infection rates followed by high rates of revisions. Microbial biofilms growing adherently on prosthetic surfaces may inhibit the detection of the pathogens causing prosthetic joint infections. We sought to answer the following questions: Does sonication culture (SC) improve the microbiological diagnosis of periprosthetic infections of megaprostheses compared to conventional tissue culture (TC)? Which pathogens were detected on the surface of megaprostheses with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
9
1
1
Order By: Relevance
“…By contrast, other authors have demonstrated that sonication fluid culture provides greater sensitivity than both tissue and synovial fluid cultures [ 17 , 18 , 22 , 23 ], possibly enhancing microbiological detection in biofilm-related orthopedic infections. Trampuz et al, were the first authors back in 2007 to found greater sensitivity for sonication cultures than for tissue cultures, and a non-statistically significant difference compared with synovial fluid cultures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, other authors have demonstrated that sonication fluid culture provides greater sensitivity than both tissue and synovial fluid cultures [ 17 , 18 , 22 , 23 ], possibly enhancing microbiological detection in biofilm-related orthopedic infections. Trampuz et al, were the first authors back in 2007 to found greater sensitivity for sonication cultures than for tissue cultures, and a non-statistically significant difference compared with synovial fluid cultures.…”
Section: Discussionmentioning
confidence: 95%
“…Both ICM 2018 and EBJIS endorsed sonication culture as an adjunct to tissue and synovial fluid cultures for diagnosing PJI [ 4 , 5 , 21 ]. In recent years, a number of authors have demonstrated that sonication fluid culture provides greater sensitivity than both tissue and synovial fluid cultures, reporting levels of 78–97% [ 17 , 18 , 22 , 23 ]. In contrast, others published their results showing a stand-in against culturing sonication fluid of retrieved implants [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, cultures have high false-negative rates and are time consuming, as they might need one to two weeks for bacteria growth, especially in patients with low-grade infections. 35,36 Targeted cloning and subsequent Sanger sequencing of 16S rDNA has also been used in the past decade, for example to identify disease-associated bacteria in clinical specimens, such as dorsal tongue and bronchoalveolar lavage fluid, 37 enamel and dentin lesions, 38 and pus from brain abscesses. 39,40 Remarkably, this approach identified many bacteria that were not previously detected in these specimens, some of which were unculturable.…”
Section: Discussionmentioning
confidence: 99%
“…Third, 16S rRNA metagenomics is strongly susceptible to contamination from reagents and sample processing, 49 which may generate false positives or false negatives. 24,50 For instance, analysis of sonicated samples may be more sensitive than analysis of whole tissues, 36,51 but additional procedures and reagents for sonication and inefficient DNA extraction also increase the risk of contamination. 21,23,52 Indeed, removal of interference from contaminating DNA is a major challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there are reports on the partial implant removal. 3,11 In our patients, we would also advise exchange for all detachable parts, in order to minimize the bacterial load and remove the biofilm, 20 if any. This may not be possible for the custom-made prostheses.…”
Section: Discussionmentioning
confidence: 99%